Pathophysiological analysis of primary biliary cirrhosis focusing on choline/phospholipid metabolism. (31st March 2014) - Kohjima, Motoyuki; Enjoji, Munechika; Yada, Ryoko; Yoshimoto, Tsuyoshi; Nakamura, Tsukasa; Fukuizumi, Kunitaka; Fukushima, Nobuyoshi; Murata, Yusuke; Nakashima, Manabu; Kato, Masaki; Kotoh, Kazuhiro; Shirabe, Ken; et al.
Abstract Background & Aims Injury to biliary epithelial cells caused by disorders in bile composition may be the initial step in the pathogenesis of primary biliary cirrhosis (PBC). We therefore examined choline/phospholipid metabolism in livers of patients with PBC. Methods Hepatic levels of mRNA encoded by choline metabolism‐related genes in early stage PBC patients were quantified by real‐time RT‐PCR. Serum cholesterol and triglyceride concentrations in each lipoprotein compartment and serum/tissue choline levels were also measured. OCT1 expression was quantified by genotype (rs683369 and rs622342). Results Serum choline concentrations were significantly higher in PBC patients than in normal individuals, with the concentrations in the former lowered by treatment with fibrates. Hepatic choline levels were markedly lower in PBC patients than in controls. The levels of expression of genes associated with choline uptake (OCT1 and CTL1), phosphatidylcholine synthesis (PEMT and BHMT), and phosphatidylcholine transport (MDR3) were significantly upregulated in PBC compared with control livers. Serum cholesterol concentrations and the cholesterol/triglyceride ratio in serum very low density lipoprotein were markedly higher in PBC patients than in controls. In PBC liver, OCT1 protein levels were lower in patients with minor (CG/GG at rs683369 and/or CC at rs622342) than major (CC at rs683369 and AA at rs622342) genotypes of the OCT1 gene. Conclusion During early stage PBC, hepatocellular choline uptake and PC synthesis become dysregulated. OCT1 genotypes may influence the pathogenesis of PBC.